2020
DOI: 10.3390/ijms22010243
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Reduces Mitochondrial Respiration in Mouse Brown Adipocytes: A Model for Disordered Energy Balance in Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrinopathy that is associated with an adverse metabolic profile including reduced postprandial thermogenesis. Although abnormalities in adipose tissue function have been widely reported in women with PCOS, less is known about direct effects of androgen on white and, particularly, brown adipocytes. The purpose of this study was to investigate the effect of the nonaromatizable androgen dihydrotestosterone (DHT) on (1) lipid accumulation and expression of adipogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…In primary brown adipocytes of rodents, testosterone inhibited mitochondrial biogenesis, brown adipocyte differentiation, and norepinephrine-induced lipolysis (115,116,124). In immortalized mouse brown adipose cells, DHT (a nonaromatizable androgen) dose-dependently inhibited differentiation, isoproterenol-stimulated Ucp1 mRNA expression, and mitochondrial respiration, and these findings were confirmed in explants of mouse BAT (133). However, direct in vivo effects of androgens appear controversial.…”
Section: Effects Of Androgens On Batmentioning
confidence: 86%
“…In primary brown adipocytes of rodents, testosterone inhibited mitochondrial biogenesis, brown adipocyte differentiation, and norepinephrine-induced lipolysis (115,116,124). In immortalized mouse brown adipose cells, DHT (a nonaromatizable androgen) dose-dependently inhibited differentiation, isoproterenol-stimulated Ucp1 mRNA expression, and mitochondrial respiration, and these findings were confirmed in explants of mouse BAT (133). However, direct in vivo effects of androgens appear controversial.…”
Section: Effects Of Androgens On Batmentioning
confidence: 86%
“…In cellular models, differentiation of brown adipocytes is inhibited by androgen in a dosedependent manner, leading to decreased expression of UCP1. These changes correspond to a reduction in the mitochondrial number and "whitening" of the interscapular BAT in androgeninduced PCOS models (140). This mitochondrial dysfunction is supported by a decrease in other mitochondrial proteins including PGC-1a and Cidea (cell death-inducing DNA fragmentation factor-like effector A).…”
Section: Androgen and Estrogen Synergy In Mitochondrial Overactivationmentioning
confidence: 83%
“…Recent studies have shown that women with PCOS have lower BAT activity compared to controls, and BAT thermogenesis and the β-adrenoceptor-stimulated increase in UCP1 expression are negatively associated with androgen levels in PCOS [24,25] . Similarly, transplantation of BAT into PCOS-like rats reverses anovulation, hyperandrogenism, and polycystic ovaries and significantly stabilizes menstruation and normalizes systemic insulin sensitivity [8] .…”
Section: Discussionmentioning
confidence: 99%